Profil Darah Ikan Nila Kunti (Oreochromis Niloticus) yang Diinjeksi Streptococcus agalactiae dengan Kepadatan Berbeda - Matofani, Ayu Shinta; Hastuti, Sri; Basuki, Fajar (Journal of Aquaculture Management and Technology, 2013)
S. agalactiae is a bacteria that often attack tilapia. The purpose of this study was to examine the blood profile of Tilapia Kunti that infected by bacterium S. agalactiae with use variable concentration of erythrocytes, leukocytes, haemoglobin, hematocrit, trombocyte, and blood glucose. The method used was a completely randomized design (CRD) with 3 treatments and 3 replications. Treatment I (Tilapia Kunti injected using S. agalactiae with density 105), treatment II (tilapia kunti injected using S. agalactiae with density107), and treatment III (tilapia kunti injected using S. agalactiae with density 109). The results showed that the tilapia kunti injected using S. agalactiae with different densities have significant differences on the hematocrit and no significant differences on erythrocytes, leukocytes, haemoglobin, trombocyte, blood glucose and survival rate. The highest concentration of erythrocytes was observed in treatment II, in the amount of 1.933 ± 0.162 x106 cells/mm3, the highest concentration of leukocytes was observed in treatment II, in the amount of 122.267 ± 3.265 x103 cells/mm3, the highest concentration of hemoglobin was observed in treatment II, in the amount of of 9.333 ± 0.404 g / dL, the highest concentration of hematocrit was observed in treatment II, in the amount of is 30.933 ± 1.168%, the highest trombocyte concentration was observed in treatment I, in the amount of 30.333 ± 14.742 x103/μL, the highest blood glucose concentrations was observed in treatment I, in the amount of 73.933 ± 47.446 mg / dL, and the highest survival rate was observed in treatment II, in the percentage of 94.443 ± 9.624%.